2020
DOI: 10.37934/arfmts.74.1.3544
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanofluids for Photovoltaic Thermal (PVT) Collectors: A Review

Abstract: Nanofluids have received considerable attention in the past decades. Nanofluid is produced by dispersing nanoparticles into a base fluid with a typical size of less than 100 nm in a liquid. Nanofluids have been proposed as a replacement for conventional cooling fluid because of their enhanced thermal properties. This review presents descriptions and previous works conducted on the performance analysis of nanofluidbased photovoltaic thermal (PVT) collectors. Results on the performance analyses of nanofluid-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…They investigated the influence of nanofluid in enhancing heat transfer in the system. The study results showed that addition of small amount of nanoparticles has significant effect in heat transfer enhancement [10].…”
Section: Introductionmentioning
confidence: 90%
“…They investigated the influence of nanofluid in enhancing heat transfer in the system. The study results showed that addition of small amount of nanoparticles has significant effect in heat transfer enhancement [10].…”
Section: Introductionmentioning
confidence: 90%
“…Traditionally, fuel or other traditional energy sources have been used to heat the air for drying agricultural and industrial goods, making the process energy-intensive (Hasan, Togun, et al 2023). However, solar energy is a potential renewable energy source for drying, which can significantly reduce energy consumption and carbon footprint(Kamaruzzaman Sopian et al 2018). Sun drying is a natural and plentiful resource that is environmentally sustainable and cost-effective compared to traditional drying methods (A-dulaimi et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cappelletti mentions that mono-crystalline PV cells have higher efficiency compared to poly-crystalline PV cells [18]. In terms of the working fluid, air is considered to be less efficient than water which itself is less efficient compared to various nanofluids [5,[19][20][21][22][23][24][25]. In terms of absorber configurations, the most common absorbers are serpentine, parallel, spiral, cross-fined absorbers amongst which, the spiral absorber is found to be the most efficient [2,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%